Peningkatan Keterampilan dan Kesadaran Gizi melalui Pelatihan Pembuatan Bakso dan Nugget di KB Permata Bunda School, Peudada, Bireuen - Rizal, Muhammad; Nurmasyitah; Hamdani; Muttaqim, Hakim; Rasyidin, M.; Saleh, M; Afriana; -, M Saleh (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This community service program aims to empower parents and teachers at KB Permata Bunda School in Peudada, Bireuen, by enhancing children’s nutritional skills and awareness through training in the preparation of nutritious meatballs and nuggets. The training was selected because meatballs and nuggets are popular among children, yet they often lack essential nutrients. Activities included the delivery of balanced nutrition material, demonstrations of nutritious meatball and nugget preparation, and hands-on practice. The results showed a significant increase in knowledge, with pretest scores rising from 30% to 85% in the posttest, reflecting a 55% improvement. Furthermore, participants’ skills in preparing nutritious food for children improved from 40% to 90%, indicating a 50% increase in competency. Overall, 90% of participants expressed satisfaction with the training and their ability to prepare nutritious meals for children.